Firm-Level Hiring Difficulties: Persistence, Business Cycle and Local Labour Market Influences - Richard Fabling; David Christopher Maré (Institute for the Study of Labor (IZA), 2013)
We examine the correlates of reported hiring difficulties at the firm level using linked employer-employee and panel survey data over 2005-2011, focussing on the relative influence of firm-level characteristics, persistence, the business cycle and local labour market liquidity. At both the aggregate and the firm-level, hiring difficulties eased after the onset of the Global Financial Crisis. Even in the presence of large cyclical changes in demand and labour market conditions, firm-level persistence is a dominant feature of the data, with one- and two-year lags of reported hiring difficulties both positively related to current difficulties. Firms paying higher wages are more likely to report difficulties when trying to hire skilled workers, while firms with more long tenure workers are less likely to report any difficulty hiring. Local labour market conditions appear unrelated to reported hiring difficulties.
Keywords: E24; J23; J63; M51; 330; hiring difficulties; hard-to-fill vacancies; local labour market; Global Financial Crisis